USULAN PERBAIKAN KURSI CUKUR PANGKAS RAMBUT ARBA BARBERSHOP MENGGUNAKAN RULA: Studi Kasus: Arba Barbershop Pondok Cilegon Indah - Panji Dewa Pamungkas; Siti Hanan; Fikri Ihza Riswanto; Prima Prima; Angga Trisna Putra; Angga Julian (LPPM Universitas Bina Bangsa, 2023)
Cutting hair is an activity that is routinely carried out by everyone, so the potential for this business is clearly large. The barbershop business was developed with the concept of maximizing the best service by offering skilled barbers, a comfortable place, an easily accessible place and a price that is perceived as reasonable. One of the supporting facilities for barbering service products is a barbering chair that is comfortable and can pamper every customer. The problem is that barbering customers when carrying out activities while shaving are still in a still state with a sitting posture for a period of 30 minutes which can cause complaints musculoskeletal. Analysis that can be done with the method Nordic Body Map and Rapid upper limb assessment (RULA), the use of this method is supported by the condition when the customer feels pain in the body when shaving, the RULA method is used for the analysis of the customer's upper body posture to improve the posture of the body during activities. Based on the data processing that has been done, it shows that the complaints felt by barbershop customers are located on the buttocks with a score of 24 complaints, the left elbow with a score of 23 complaints, and the right elbow with a score of 22 complaints. C, A & E. RULA analysis of barbershop customers who have been analyzed based on observations A and B, a final score of 5 is obtained, meaning that investigations and changes in work posture must be carried out as soon as possible musculoskeletal